Laser surface modification of duplex stainless steel 2205 to modify the surface roughness - Y., Arsyad; Linggam, R.; Quazi, M. M.; Aiman, Mohd Halil; M., Ishak; A. Q., Zaifuddin; Qaban, Abdullah (Penerbit Universiti Malaysia Pahang, 2021)
Laser surface modification is an emerging process that can produce texture on a work surface and effectively enhance surface topography while altering surface roughness. Laser surface modification is a sensitive process that depends on various laser processing parameters such as power, scanning speed, hatching distance. The significance of this work is to examine the influence of hatching distance on the surface characteristic of 2205 duplex stainless steel samples. The surface transformation and variation of the surface roughness properties of the materials were examined. The hatching distance was varied from 0.1 to 0.005 mm. Results indicate that, as the hatch spacing decreases, the overlap of laser track increases, thereby resulting in a decrease of surface roughness. Meanwhile, with the increase of hatch distance, the clear overlay tracks were transformed to irregular wavy surface. The best hatch distance parameter obtained was 100 μm that resulted in the highest roughness of 8.45 μm. Experimental results illustrate that, when the optimum hatch distance of 100 μm was adopted, the polished smooth surface of 2205 duplex stainless steel with initial average roughness value of 0.19 μm increased by 42 times of the polished surface roughness. A strong correlation between hatching distance and roughness was established in 2205 duplex stainless steel. High depth of the altered surface topography and increased roughness were linked to higher levels of hatching distance.